Pengaruh Literasi Keuangan dan Locus of Control Terhadap Perilaku Keuangan Mahasiswa Universitas Teuku Umar - Syafitri, Syafitri; Muzakir, Muzakir; Mandaraira, Fitria (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
In the era of rapid financial technology development, university students are expected to possess the ability to manage their finances wisely in order to avoid excessive consumer behavior. However, in reality, many students are still unable to manage their finances effectively. Therefore, adequate financial literacy and strong self-control in financial decision-making are essential. This study aims to examine and analyze the influence of financial literacy and locus of control on the financial behavior of students at Teuku Umar University. This research employed a quantitative approach with a sample of 383 students from Teuku Umar University selected through random sampling. The data used in this study were primary data collected through questionnaires measuring financial literacy, locus of control, and students’ financial behavior. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that financial literacy and locus of control have a positive and significant effect on students’ financial behavior, both partially and simultaneously. These findings imply that higher levels of financial literacy and stronger locus of control are associated with better financial behavior among students in managing their personal finances.